Cleveland adolescent sleepiness questionnaire (CASQ): sleep pattern among undergraduates in Malaysia - Munizam Halik; Lim, Ai Xuan; Ferlis Bahari (Universiti Malaysia Sabah, 2015)
Daytime sleepiness among adolescents is nearly universal; the sleep/wake rhythm in humans is regulated by the circadian timing system that makes people to be sleepy at certain times of the day. Research suggests academic performance is affected by lack of sleep may influence hence the importance of this study at tertiary level. A survey of 707 full-time undergraduates at a local university in Malaysia was conducted using a modified Cleveland Adolescent Sleepiness Questionnaire. The modified CASQ was found to be reliable and significant and thus suitable to be used to measure students daytime sleepiness. Results showed that male students (n=237) reported significantly higher daytime sleepiness. There is a significant difference between academic performance and sleepiness and science stream students are more likely to record higher sleepiness compared to non-science student. There is a need to increase awareness of this problem in the education and to further research on this phenomenon in the Malaysian context.